Latest Pliocene Northern Hemisphere glaciation amplified by intensified Atlantic meridional overturning circulation - Tatsuya Hayashi (Nature Portfolio, 2020)
Active overturning in the Nordic seas and strong Atlantic circulation coincided with enhanced glaciation in the Northern Hemisphere after 2.7 Ma, according to a multi-proxy investigation of cores from the IODP site U1314.